First experiences of photoacoustic imaging for detection of melanoma metastases in resected human lymph nodes - Grootendorst, D.J.; Jose, J.; Wouters, M.W.; van Boven, H.; Van der Hage, J.; Van Leeuwen, T.G.; Steenbergen, W.; Manohar, S.; Ruers, T.J.M. (Lasers in surgery and medicine, 2012)
Background and Objective Excision and histological assessment of the first draining node (sentinel lymph node) is a frequently used method to assess metastatic lymph node involvement related to cutaneous melanoma. Due to the time required for accurate histological assessment, nodal status is not immediately available to the surgeon. Hence, in case histological examination shows metastases, the patient has to be recalled to perform additional lymphadenectomy. To overcome these drawbacks we studied the applicability of photoacoustic tomographic imaging as an intra‐operative modality for examining the status of resected lymph nodes. Materials and Methods In melanoma patients undergoing lymphadectomy for metastatic disease, six suspect lymph nodes were photoacoustically (PA) imaged using multiple wavelengths. Histopathologal examination showed three nodes without tumor cells (benign nodes) and three nodes with melanoma cells (malignant nodes). PA images were compared with histology and anatomical features were analyzed. In addition, PA spectral analysis was performed on areas of increased signal intensity. Results After correlation with histopathology, multiple areas containing melanoma cells could be identified in the PA images due to their increased response. Malignant nodes showed a higher PA response and responded differently to an increase in excitation wavelength than benign nodes. In addition, differences in anatomical features between the two groups were detected. Conclusions Photoacoustic detection of melanoma metastases based on their melanin content proves to be possible in resected human lymph nodes. The amount of PA signal and several specific anatomical features seem to provide additional characteristics for nodal analysis. However, it is as yet preliminary to designate a highly accurate parameter to distinguish between malignant and benign nodes. We expect to improve the specificity of the technique with a future implementation of an adjusted illumination scheme and depth correction for photon fluence. Lasers Surg. Med. 44: 541–549, 2012. © Wiley Periodicals, Inc.